Viewpoints on Ruling by Law in The Philosophical Thought of Han Fei Tzu - Tuoi, Duong Thi (Jurnal Cita Hukum, 2024)
During the Spring Autumn and Warring States periods, when Chinese society was in chaos and instability, Han Fei Tzu proposed a comprehensive view that law is the most effective tool to bring peace, stability, and justice. This approach, which stands in stark contrast to the contemporary emphasis on morality and virtue in governance, holds relevance even in modern times. The primary aim of this study is to elucidate the role of law in politics from a philosophical perspective, with a specific focus on Han Fei Tzu's thoughts on the application of law as the primary instrument in state governance. The study employs a qualitative method, comprising two main approaches: the literature approach and the law approach. The literature approach is used to analyze classical texts and philosophical works that discuss Han Fei Tzu's thoughts on law and governance, and to review modern academic literature that either supports or criticizes his views. Meanwhile, the law approach is used to assess how Han Fei Tzu's proposed concept of law can be implemented in the context of governance and whether its application aligns with modern legal theory. The findings underscore the importance of Han Fei Tzu's thoughts on law, which stress the need for consistency between theory and practice, and the comprehensive enforcement of law without any discrimination. His thinking also underscores the significance of law as a tool of social control that is not contingent on individual morality, but on absolute obedience to the rules set by the state. The study raises several critical questions about the relevance of Han Fei Tzu's views in the context of modern politics, and offers recommendations for further research on the role of law in achieving sustainable political stability.